Eight proxy indices of solar activity for the International Reference Ionosphere and Plasmasphere model. (July 2018) - Gulyaeva, T.L.; Arikan, F.; Sezen, U.; Poustovalova, L.V.
Abstract: In view of the recent recalibration of the sunspot number time series SSN2, a need has arisen to re-evaluate solar and ionospheric indices in the International Reference Ionosphere, IRI, and its extension to the Plasmasphere, IRI-Plas models, which are developed using the predecessor SSN1 index. To improve efficiency of the model, eight solar proxy indices are introduced in IRI-Plas system: the daily measured solar emissions, the Ottawa 10.7-cm radio flux F10.7 and the H Lyman-α line at 121.6 nm; the core–to–wing ratio of the magnesium ion h and k lines at 279.56 and 280.27 nm, MgII index; sunspot number SSN1 observed before 05.2015 and modelled afterwards; re-calibrated SSN2 sunspots time series; the ionosonde foF2-based global IG -index and the Global Electron Content, GEC, index, the new ionospheric TEC -noon index based on GPS-derived Total Electron Content measurements at 288 IGS stations for 1994–2018. The regression relations are deduced between the different solar and ionospheric proxy indices smoothed by 12-month sliding window. The IG, TEC and GEC saturation or amplification effect is observed towards the solar maximum. The SSN1 and F10.7 data serve as a default IRI-Plas input while the rest indices are scaled to SSN1 units envisaged by the F2 layer peak maps. Relevant subroutines are incorporated in IRI-Plas system for automatic conversion of user's predefined index to other related indices which are applied by the different model procedures. Highlights: Eight solar proxy indices are incorporated in IRI-Plas model for 1948–2020 including predictions out of period of observation. Ionospheric proxies are IG-foF2, TEC-noon, Global electron content GEC. Solar proxies include SSN1, SSN2, F10.7, Lyman-alpha, MgII. Relations established between all solar proxies. Saturation or amplification effect is observed with several proxies towards solar maximum.